Coupling electromagnetic numerical models of HTS coils to electrical circuits: multi-scale and homogeneous methodologies using the T-A formulation. (1st November 2022) - Zhou, Pengbo; Dos Santos, Gabriel; Ghabeli, Asef; Grilli, Francesco; Ma, Guangtong
Abstract: Numerical simulation is an effective tool for predicting the electromagnetic behavior of superconductors. Recently, a finite element method-based model coupling the T - A formulation with an electrical circuit has been proposed: the model presents the superconducting constituent as a global voltage parameter in the electrical circuit. This allows assessing the overall behavior of complex high-temperature superconductor (HTS) systems involving multiple power items, while keeping a high degree of precision on the presentation of local effects. In this work, the applicability of this model has been extended to large-scale HTS applications with hundreds or thousands of tapes by referring to two widely recognized methodologies, multi-scale and homogenization, to improve the computation efficiency. Based on the two approaches, three different models were developed and their effectiveness was assessed using the case study of a 1000 turn cylindrical HTS coil charged by a DC voltage source. The comparison of the calculated global circuit parameters, local field distributions, losses, and computation time proves that the computation efficiency can be improved with respect to a model simulating all HTS tapes, without compromising accuracy. The results indicate that the developed models can therefore be efficient tools to design and optimize large-scale HTS devices used in electrical machines and power grids. It is also found that the inductance of an HTS coil is varied according to the transport current and can be even higher than that of a normal conductor coil with the same geometry. We attribute this result to the superconductor's non-uniform current distribution and relaxation effect during the dynamic process.